Figures of the Psychotherapist in Contemporary Chinese Literature - Guo, Lanfang; Yuan, Wei (Frontiers in Psychology, 2022)
Since the 1980s, psychoanalysis and psychotherapy have attracted great interest in Chinese society, and in parallel, the psychotherapist as a character has emerged in Chinese literature. Through four novels by three Chinese authors, namely, Xu Xiaobin 徐小斌, Ke Yunlu 柯云路, and Bi Shumin 毕淑敏, this article studies the evolution of the image of the psychotherapist in contemporary Chinese literature, which reflects the reception of psychoanalysis as well as the development of psychotherapy in China. In Xu Xiaobin’s novel, two psychology students attempt to cure a psychotic patient through “transference therapy” based on a complete misunderstanding of the notion; Ke Yunlu features a “life counselor” who, like typical good counselors in Chinese classical novels, simply gives advice without caring about the patients’ needs and desires; and the two novels by Bi Shumin show a significant change in the writer’s understanding of the profession and therapeutic methods, as well as the current, unregulated situation of psychotherapy in China.